The effect of date fruit consumption on delivery outcomes: A systematic review - Kharizmatika; Soediono, Mochammad Ridhwan (Universitas Airlangga, 2026)
HIGHLIGHTS Consuming date fruit in late pregnancy may enhance labor outcomes by reducing labor duration, speeding up cervical dilation, and decreasing the need for induction. Healthcare providers might recommend it as a natural dietary intervention, while further research should standardize protocols and determine optimal dosages. ABSTRACT Objective: This systematic review examines the impact of date fruit consumption during pregnancy on labor and delivery outcomes. Materials and Methods: A systematic search was carried out utilizing PubMed, Cochrane Library, and ScienceDirect databases to identify systematic reviews and meta-analyses published within the last five years. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria were adhered to in order to identify studies and extract data. Quality evaluation was carried out utilizing the AMSTAR tool to ensure methodological rigor. Results: Among 3,528 initial records, 255 articles met eligibility criteria, with 4 systematic reviews included for analysis. Date fruit consumption was associated with shortened first stage of labor (pooled effect size: -50.09 to -76.16 minutes), reduced second stage duration (pooled effect size: -7.7 to -15.05 minutes), accelerated cervical dilatation (pooled effect size: 0.94 to 1.15 cm), and decreased gestation duration (pooled effect size: -0.30 weeks to -1.97 days). Improved Bishop score (MD/WMD: 2.45 to 2.47) and decreased labor induction frequency (RR: 0.48 to 0.6) were also observed. Heterogeneity in outcomes suggests variable effects across studies. Conclusion: Date fruit consumption in late pregnancy shows potential benefits for labor outcomes, including shorter duration of labor stages, accelerated cervical dilation, and reduced need for labor induction. Healthcare providers may consider recommending date fruit as a natural dietary intervention to enhance maternal and neonatal health during childbirth. Further research should standardize protocols, explore optimal dosages, and elucidate mechanisms to strengthen evidence-based recommendations.